Implementasi Corporate Social Responsibility PT PLN Dalam Pemberdayaan Masyarakat Dan Lingkungan Melalui Program “PLN PEDULI” - Siti Qonaah (Jurnal Komunikasi, 2018)
Abstract - community empowerment and environment with theme "PLN Peduli” is an implementation of Corporate Social Responsibility program implemented by PT PLN Year 2017. This Corporate Social Responsibility Program utilizes good management system and environment which is developing pandansari tourism village through community empowerment and development of natural resources potency in Pandasari Batang Central Java . This study aims to determine the Implementation of Corporate Social Responsibility PT PLN In Community Empowerment and Environment Through Program "PLN Peduli”  (Case Study On CSR Program PT PLN Through "Community Empowerment and Environment in Deswita Pandansari District Batang Central Java) In this research, the researcher uses qualitative approach and case study, as a research method which gives an idea that "PLN Peduli" is part of corporate social responsibility community empowerment and environment  in Pandansari Batang Central Java. thus the corporate social responsibility program with the theme of "PLN Peduli" through the empowerment of society and the Environment can improve the welfare of the community and the management communityKeywords: Corporate Social Responsibility, Community Empowerment